How to manage thromboembolic risk in patient with SARS-CoV-2-related disease in the Emergency Department: A case report of cardiogenic shock due to massive pulmonary embolism. (2020) - Colombo, L.; Macheda, A.; Gentile, D.; Panizzardi, F.; Pierini, S.; Codazzi, C.; Meloni, L.; Bianchi, F.; Santangelo, G.
Abstract: Background: Although the most known feature of SARS-CoV-2 associated infection is a mild to severe pneumonia, increasing evidence suggests the existence of an infection-associated risk of both arterial and venous thromboembolism (VTE), but the exact magnitude of this phenomenon is still unknown. Given that, it is important for the Emergency Physician to remember that a SARS-CoV-2 associated respiratory failure can be caused not only by the pulmonary parenchymal inflammation that characterizes the pneumonia, but also by an associated pulmonary thromboembolism. Case report: A healthy 73-years old woman admitted to the ED for dyspnea, fever and thoracic pain. Cardiac ultrasound, electrocardiogram and clinical findings suggested a diagnosis of cardiogenic obstructive shock due to acute pulmonary embolism, successfully treated with thrombolysis. A CT angiography confirmed the pulmonary embolism (EP) diagnosis and showed bilateral pneumonia, caused by SARS-CoV-2 infection. Conclusion: Considering the high prevalence of thromboembolic events in COVID-19 patients it is mandatory for the emergency physician to systematically evaluate signs of pulmonary thromboembolism, in order to perform the most patient-tailored therapy as soon as possible.